The Effect of Monetary Changes on Interest Rates: A Comment - Kang, Heejoon (The Review of Economics and Statistics, 1983)
Singh, Balvir, Helmar Drost and Ramesh C. Kumar, An Empirical Evaluation of the Relative, the Permanent Income and the Life-Cycle Hypotheses, Economic Development and Cultural Change 26 (Jan. 1978), 281-305. Singh, Balvir A., and Aman Ullah, Consumption Function: The Permanent Income versus the Habit Persistence Hypothesis, this REVIEW 58 (Feb. 1976), 96103. U.S. Department of Commerce, Expenditures, and Wealth, The Statistical A bstrac t of the U.S., 1942. ______, National Product and Income, Historical Statistics of the United States, Colonial Times to 1970, Bicentennial ed., Part I (Washington, D.C., 1975), 225.